A contribuição dos traços de perfeccionismo, mediada pela motivação, para a coesão de grupo no futsal de alto rendimento - Nascimento Junior, José Roberto Andrade do (2015)
The objective of this thesis was to investigate the contribution of perfectionism traits, mediated by motivation, on the perception of team cohesion among high performance futsal athletes. To achieve this goal, the first two papers involved the cross-cultural adaptation and validation of the Basic Needs Satisfaction in Sport Scale and the Sport Multidimensional Perfectionism Scale-2 for the Brazilian context with 395 adult athletes of both gender, participants of the final phase of the Open Games Paraná-2012, which showed satisfactory psychometric properties after exclusion of 8 and 18 items, respectively. The analysis of the mediating role of motivation through the basic needs in the contribution of perfectionism traits on the perception of team cohesion in the futsal context involved the third original article and the thesis was performed with 301 athletes participating of the Futsal National League in 2013. The results showed significant relationships of the perfectionistic concerns and striving with the motivation through the basic needs of competence, autonomy and relatedness (shared variance of 15%); Further, the basic needs significantly mediated the relationship between perfectionism and team cohesion, whereas the mediation model explained 16% of the variability of the athletes' perceived team cohesion. Relatedness was the basic need that demonstrated greatest impact on team cohesion when preditcted by perfectionism, while perfectionistic striving had greater impact on autonomy. To analyze the relationship between perfectionism, motivation and team cohesion along the phases of sports development, the fourth original article included a qualitative analysis of interviews of 25 elite futsal athletes. The findings indicated that, since childhood, players had strong characteristics of adaptive and maladaptive perfectionism, presence ofself-determined motivation and strong cultural identification and internalization with the sport (controlled motivation), as well as ease of communication, teamwork and the taste for competition (social and task cohesion). It was concluded that, within the high performance Brazilian futsal context, athletes with adaptive perfectionism traits and satisfied with their basic needs of motivation have higher chances to increase their team cohesion perceptions. In addition, the basic needs of motivation may contribute to the effect of adaptive perfectionism on the athletes' perception of cohesion and prevent the impact of maladaptive perfectionism. These characteristics have become more evident according as the athletes have evolved over the stages of sports development.